Kissing architecture - Lavin, Sylvia (Point: essays on architecture, 2011)
Kissing Architecture explores the mutual attraction between architecture and other forms of contemporary art. In this fresh, insightful, and beautifully illustrated book, renowned architectural critic and scholar Sylvia Lavin develops the concept of "kissing" to describe the growing intimacy between architecture and new types of art--particularly multimedia installations that take place in and on the surfaces of buildings--and to capture the sensual charge that is being designed and built into architectural surfaces and interior spaces today. Initiating readers into the guilty pleasures of architecture that abandons the narrow focus on function, Lavin looks at recent work by Pipilotti Rist, Doug Aitken, the firm Diller Scofidio + Renfro, and others who choose instead to embrace the viewer in powerful affects and visual and sensory atmospheres.